Marketing Research and Forecasting Demand: Strategies for Optimizing Sales - Maghfirotus Safitri, Isabna; Lailatul Hibah; Ayu Lestari; Rinda Asytuti (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2024)
Marketing plays a crucial role in understanding consumer needs, behavior, and market opportunities. However, many companies face challenges in effectively utilizing marketing research. This paper identifies barriers such as narrow conceptions of research, inadequate researcher quality, and poor problem framing. Following research completion, demand forecasting becomes essential. Accurate measurement of market size, growth, and profit potential is vital to avoid inventory discrepancies affecting company performance. Various methods, including market formation and multifactor index, are employed to estimate market potential, each with its advantages and limitations. Global marketing research involves a systematic process, aiding companies in understanding global markets, reducing uncertainty, and enhancing marketing innovation. Understanding the significance of marketing research and forecasting empowers companies to make